PERANCANGAN RANGKAIAN PENGONDISI SINYAL UNTUK SENSOR PENGINDERAAN JAUH - Taufiq, Arif Johar (UMP, 2012)
It has done the design of signal conditioning for remote sensing sensor to anticipate disturbance magnetic field null offset and inteference above 50Hz. The result of Workbench simulation obtained the signal conditioning circuit can work properly and can anticipate the magnetic field disturbances null offset and interference frequencies above 50 Hz.Â Keyword: penginderaan jauh, pengondisi sinyal, LPF Butterworth